2019
DOI: 10.1021/acs.analchem.9b02238
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Mobility Quadrupole Time-of-Flight Mass Spectrometry: A Novel Technique Applied to Migration of Nonintentionally Added Substances from Polyethylene Films Intended for Use as Food Packaging

Abstract: Nontarget analysis of nonvolatile substances in complex samples is a very challenging task that requires powerful analytical techniques and experience of analyzing such samples. An extensive study was conducted in order to identify nonintentionally added substances (NIAS) migrating from 18 polyethylene (PE) samples intended to be in contact with food. The migration assays were performed in five simulants and analyzed by ultrahigh-performance liquid chromatography (UPLC) coupled to an ion-mobility separation (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…Due to the fact that oleamide was found to be leaching from some plastic and other labware by our previous study [24], its presence in polymeric containers for food/beverages and medicines and its consequent leaching into the polymer contact liquid was assumed. Migration of oleamide from polymer starting materials used in food packing [9,[25][26][27], food storage containers [28,29] or plastic baby bottles [10] into some food simulants was already reported. Oleamide leaching from baby bibs has also been assessed [30].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that oleamide was found to be leaching from some plastic and other labware by our previous study [24], its presence in polymeric containers for food/beverages and medicines and its consequent leaching into the polymer contact liquid was assumed. Migration of oleamide from polymer starting materials used in food packing [9,[25][26][27], food storage containers [28,29] or plastic baby bottles [10] into some food simulants was already reported. Oleamide leaching from baby bibs has also been assessed [30].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, and as provided by legislation ((EU) n° 10/2011), the migration study is performed with food simulants in place of the food itself, due to the high complexity that food has typically as a matrix than foods [ 29 , 58 , 59 ]. They should represent the significant physicochemical properties exhibited by each food type.…”
Section: Migration Of Substances From Packaging To the Foodmentioning
confidence: 99%
“…Table 4 listed scientific publications that determined breakdown products in different types of plastic food packaging. Most of the studies reported degradation products as NIAS, and most of the reported NIAS are degradation products from the antioxidants Irganox 1010 and Irgafos 168 [ 59 , 70 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Nias In Plastic Food Packagingmentioning
confidence: 99%
“…Several data acquisition strategies were reported, including Data Independent Acquisition ( all of them may be relevant. In two recent studies Vera et al, 2019), the use of ion mobility MS (IMS) was presented as a way to reduce background noise during acquisition, through drift-time alignment. Through this process, they demonstrated that matrix-interferences can be reduced substantially, leading to cleaner spectra.…”
Section: Comprehensive Suspect Screening and Non-target Analysismentioning
confidence: 99%